2021
DOI: 10.47102/annals-acadmedsg.2021213
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and trends in the adoption of laparoscopic liver resection in Singapore: Analysis of 300 cases

Abstract: Introduction: The introduction of laparoscopic surgery has changed abdominal surgery. We evaluated the evolution and changing trends associated with adoption of laparoscopic liver resection (LLR) and the experience of a surgeon without prior LLR experience. Methods: A retrospective review of 310 patients who underwent LLR performed by a single surgeon from 2011 to 2020 was conducted. Exclusion criteria were patients who underwent laparoscopic liver surgeries such as excision biopsy, local ablation, drainage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The aim would be for the DSS to accurately discriminate LLR based on its technical difficulty to allow surgeons at different stages of the learning curve to attempt cases suitable for their skill and experience level. 47,48 This also allows a standardized approach to auditing outcomes and comparing results between centres and countries, 49,50 as well as comparing outcomes between approaches, such as LLR compared to RLR. 51 Our systematic review found 11 unique DSS.…”
Section: Discussionmentioning
confidence: 99%
“…The aim would be for the DSS to accurately discriminate LLR based on its technical difficulty to allow surgeons at different stages of the learning curve to attempt cases suitable for their skill and experience level. 47,48 This also allows a standardized approach to auditing outcomes and comparing results between centres and countries, 49,50 as well as comparing outcomes between approaches, such as LLR compared to RLR. 51 Our systematic review found 11 unique DSS.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]14 These challenges may be partially overcome by using the lateral position, additional intercostal trocars, and the flexible tip laparoscope. [6][7][8][15][16][17] Nonetheless, despite the greater complexity, LLR of segments 7 and 8 have shown the known advantages of minimally invasive surgery over the open approach such as significantly lower blood loss and length of hospital stay. 15,18 To date, there are no head-to-head comparative studies between LLR of Segments 7 and 8.…”
Section: Discussionmentioning
confidence: 99%
“…When adopting the laparoscopic approach, the difficulty of these resections is further augmented due to the caudal‐cranial view impairing adequate visualization of the operative field and difficulty of the rigid laparoscopic instruments accessing these areas 6–8,14 . These challenges may be partially overcome by using the lateral position, additional intercostal trocars, and the flexible tip laparoscope 6–8,15–17 . Nonetheless, despite the greater complexity, LLR of segments 7 and 8 have shown the known advantages of minimally invasive surgery over the open approach such as significantly lower blood loss and length of hospital stay 15,18 …”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, resection for tumours located in the difficult segments continue to be less widely performed due to the technical challenges of the procedures resulting in increased risk of nononcological resections or uncontrollable bleeding. [28][29][30][31] The caudate lobe with its peculiar anatomy has a history of changing definitions and classifications. [7][8][32][33] It is widely considered to be the one of the most difficult liver segments to approach surgically.…”
Section: Discussionmentioning
confidence: 99%
“…In many specialized liver centres, less complicated liver resections such as left lateral sectionectomies are now routinely performed via the minimally invasive approach 26,27 . However, resection for tumours located in the difficult segments continue to be less widely performed due to the technical challenges of the procedures resulting in increased risk of non‐oncological resections or uncontrollable bleeding 28–31 …”
Section: Discussionmentioning
confidence: 99%